2015
DOI: 10.1242/jcs.168583
|View full text |Cite
|
Sign up to set email alerts
|

mRNA encoding Sec61β, a tail-anchored protein, is localized on the endoplasmic reticulum

Abstract: Although one pathway for the post-translational targeting of tail-anchored proteins to the endoplasmic reticulum (ER) has been well defined, it is unclear whether additional pathways exist. Here, we provide evidence that a subset of mRNAs encoding tail-anchored proteins, including Sec61β and nesprin-2, is partially localized to the surface of the ER in mammalian cells. In particular, Sec61b mRNA can be targeted to, and later maintained on, the ER using both translation-dependent and -independent mechanisms. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 50 publications
(92 reference statements)
1
20
0
Order By: Relevance
“…Transferrin receptor (TFRC) transcripts, which encode a membrane protein, were resistant to extraction (71%) and, thus, likely to be ER associated ( Figure 1B). This is similar to what was previously found for other mRNAs encoding membrane-bound and secretory proteins (Cui et al, , 2015Jagannathan et al, 2014). In contrast, only a minority of mRNAs encoding cytosolic or nuclear proteins-glyceraldehyde-3-phosphate dehydrogenase (GAPDH), DnaJ heat-shock protein family (Hsp40) member B4 (DNAJB4), forkhead box K2 (FOXK2) transcription factor, and 5 0 -nucleotidase domain containing protein 2 (5NTDC2)-was resistant to digitonin extraction.…”
Section: A Subset Of Mrnas Encoding Cytosolic and Nuclear Proteins Issupporting
confidence: 83%
“…Transferrin receptor (TFRC) transcripts, which encode a membrane protein, were resistant to extraction (71%) and, thus, likely to be ER associated ( Figure 1B). This is similar to what was previously found for other mRNAs encoding membrane-bound and secretory proteins (Cui et al, , 2015Jagannathan et al, 2014). In contrast, only a minority of mRNAs encoding cytosolic or nuclear proteins-glyceraldehyde-3-phosphate dehydrogenase (GAPDH), DnaJ heat-shock protein family (Hsp40) member B4 (DNAJB4), forkhead box K2 (FOXK2) transcription factor, and 5 0 -nucleotidase domain containing protein 2 (5NTDC2)-was resistant to digitonin extraction.…”
Section: A Subset Of Mrnas Encoding Cytosolic and Nuclear Proteins Issupporting
confidence: 83%
“…To explain the discrepancy between the precise in vivo targeting of b5‐ER and b5‐RR and their promiscuous behavior in cell‐free systems, we considered the possibility that the capacity of the 2 forms to discriminate between the ER and the MOM might depend on a segregated localization of their mRNAs, as reported for Sec61β, or on ribosome‐associated factors, which would capture the substrate immediately after the release from the ribosome . If either of these mechanisms were operating, the purified recombinant proteins, microinjected into the cytosol of cultured cells, would be incapable of correct targeting.…”
Section: Resultsmentioning
confidence: 99%
“…Another potential mechanism could be contributed by mRNA localization . In the case of TA proteins, Cui et al reported that the mRNAs coding for Sec61β and for nesprin are partially localized to the ER, thus facilitating the subsequent insertion of the translated polypeptides. Finally, the precision of TA protein localization can be fine‐tuned by postinsertional quality control mechanisms, as exemplified by the AAA ATPase Msp1/ATAD, which extracts mislocalized TA proteins from the MOM for subsequent degradation …”
Section: Discussionmentioning
confidence: 99%
“…This might especially be true in cases where the mRNA may localize right near its translational product, especially for many organelle‐targeted transcripts. For example, Sec61β mRNA, which encodes a tail‐anchored protein that is a component of the translocon (the main protein‐conducting pore of the ER), localizes to the ER membrane . This is surprising, since tail‐anchored proteins are thought to be inserted into membranes post‐translationally placing their mRNAs in the cytosol .…”
Section: Localized Mrna Regulation a General Phenomenon For Organellmentioning
confidence: 99%
“…This is surprising, since tail‐anchored proteins are thought to be inserted into membranes post‐translationally placing their mRNAs in the cytosol . Interestingly, the overexpression of GFP‐Sec61β evicts other mRNAs from the ER surface, probably because its mRNA saturates all the mRNA‐binding sites on this organelle (i.e., ribosomes that are docked onto the translocon) . It is possible that the endogenous Sec61β mRNA is translated only when there is an excess of translocon that lacks its encoded protein Sec61β.…”
Section: Localized Mrna Regulation a General Phenomenon For Organellmentioning
confidence: 99%